Clarifying phenomenologies in the study of religion: separating Kristensen and van der Leeuw from Otto and Eliade. Issue 1 (2nd January 2016) - Tuckett, Jonathan
Abstract : One of the most difficult aspects of trying to understand 'phenomenology' in the study of religion is that proponent and opponent alike cannot seem to agree on what the title actually entails. Yet despite an insistence that 'phenomenology' does not refer to a monolithic tradition, many scholars still write as if it is, subsuming a range of contradictory figures under the rubric. It is the argument of this paper that Kristensen and van der Leeuw have been victims of this 'Tyranny of the Same' which has occluded their methodological value. By questioning their relation to Rudolf Otto and Mircea Eliade – common representatives of 'phenomenology of religion' – the author will argue that each pair represents a different tradition: typological phenomenology and phenomenological history-of-religion. Their erroneous connection, the author argues, has been the product of a third, synthetic tradition: phenomenology-of-religion.